Use of temporary double-J stent placement for children with congenital hydronephrosis: a long-term single-center cohort study - Hutflesz, Nina; Boettcher, Michael; Deeg, Susanne; Stein, Raimund; Wessel, Lucas; Zahn, Katrin (Urology, 2023)
Objective - To evaluate the utilization of double-J stents in children with congenital hydronephrosis in order to avoid or postpone more invasive surgical intervention. Numerous studies have demonstrated that congenital hydronephrosis caused by ureteropelvic junction obstruction (UPJO) or primary obstructive megaureter (POM) may require a surgical correction in up to 20% of cases. - Methods - All infants with severe hydronephrosis and/or an obstructive pattern on renal scintigraphy that received double-J stent placement between 2010 to 2015 in our center were analyzed. Children were followed regularly with ultrasound and received antibiotic metaphylaxis. Urinary tract infection (UTI) and double-J dislocation were defined as complications. Treatment success was defined as avoidance of surgery and reduction of hydronephrosis to grade 1 or 0 during the observation period. - Results - 29 children were included, in these, 34 (23 UPJO, 7 POM, 4 UPJO and POM) treatment attempts were performed. Stent implantation failed in six cases, resulting in 28 double-J stent treatments, of which 19 (69%) were successful within the follow-up period of 20 to 104 months. The most common complications were febrile UTI in 6 of29 cases and double-J dislocation in 3 of 29 cases. - Conclusion - During the observation period, the success rate of temporary double-J in urodynamically relevant obstruction was relatively high. However, urinary tract infections and a complex disease course due to renal stent dislocation, as well as the need for repeated anesthesia and radiation exposure, should be taken into account. Hence, we do not recommend double-J stents placement in all children with congenital hydronephrosis; it may be useful in selected cases.
Online verfügbar: 5. Dezember 2022, Artikelversion: 22. März 2023
Gesehen am 15.07.2024